1979
DOI: 10.1002/1097-0142(197903)43:3<1123::aid-cncr2820430351>3.0.co;2-f
|View full text |Cite
|
Sign up to set email alerts
|

Radiation therapy for localized prostate cancer

Abstract: Since 1965,401 patients with prostate cancer have received intensive local pelvic radiation therapy at the Virginia Mason Medical Center. Two hundred seventyseven of these patients were treated from 1965 through 1975, comprising the study group. Two hundred twenty-one of this series were in the Stage C category.The 36 Stage B cancers were either medically nonoperable, or advanced extent, or had high-grade histopathology. Ten patients each were in diffuse Stage A or Stage D groups, the latter receiving local pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

1986
1986
1999
1999

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 50 publications
(3 citation statements)
references
References 18 publications
0
3
0
Order By: Relevance
“…Three controlled clinical trials have failed to demonstrate the value of prophylactic therapy with diethylstilbestrol, orchiectomy, or both in patients treated with external radiotherapy. [6][7][8] A study of 277 patients found no differences among those undergoing orchiectomy, radiotherapy, or combined treatment; orchiectomy, however, whether alone or combined with radiotherapy, significantly delayed metastases as compared with radiotherapy alone. 9 Goserelin is an agonist analogue of gonadotropinreleasing hormone that induces hypogonadism by reducing the secretion of gonadotropin and therefore testosterone.…”
Section: Resultsmentioning
confidence: 99%
“…Three controlled clinical trials have failed to demonstrate the value of prophylactic therapy with diethylstilbestrol, orchiectomy, or both in patients treated with external radiotherapy. [6][7][8] A study of 277 patients found no differences among those undergoing orchiectomy, radiotherapy, or combined treatment; orchiectomy, however, whether alone or combined with radiotherapy, significantly delayed metastases as compared with radiotherapy alone. 9 Goserelin is an agonist analogue of gonadotropinreleasing hormone that induces hypogonadism by reducing the secretion of gonadotropin and therefore testosterone.…”
Section: Resultsmentioning
confidence: 99%
“…The 5-year local control rates for locally advanced prostatic cancer after high-dose photon therapy range between 54% and 68% (58)(59)(60)(61)(62)(63)(64). Results of neutron therapy has been studied at several centers in the United States and Europe.…”
Section: Prostate Adenocarcinomamentioning
confidence: 99%
“…
During the years 1976 to 1982 definitive curatively aimed radiotherapy to the primary tumor was given to 53 patients with prostatic cancer confined to the true pelvis (To,2;19; T3,24; Tq,8; No,18; N,,2; N,, 33); all patients were of the Mo-category. The pelvic lymph nodes received a total dose of 2 Gy X 25 by means of an anterior and posterior radiation field.
…”
mentioning
confidence: 99%